Evaluasi Implementasi Pasal 33 UUD 1945 terhadap Pengelolaan Kekayaan Alam Nasional - Muhammad Kandriana (Jurnal Hukum Lex Generalis, 2025)
Article 33 of the 1945 Constitution serves as the constitutional foundation for natural resource governance aimed at the greatest prosperity of the people. In practice, its implementation through sectoral regulations remains fragmented, marked by weak supervision and the dominance of economic interests over social justice and environmental sustainability. The analysis reveals a significant gap between constitutional mandates and actual governance practices. Therefore, legal reform emphasizing regulatory integration, strengthened governance and ecological justice principles is essential to achieve equitable and sustainable natural resource management.